2005
DOI: 10.1152/japplphysiol.00620.2004
|View full text |Cite
|
Sign up to set email alerts
|

Increased sympathetic and decreased parasympathetic cardiovascular modulation in normal humans with acute sleep deprivation

Abstract: Cardiovascular autonomic modulation during 36 h of total sleep deprivation (SD) was assessed in 18 normal subjects (16 men, 2 women, 26.0 +/- 4.6 yr old). ECG and continuous blood pressure (BP) from radial artery tonometry were obtained at 2100 on the first study night (baseline) and every subsequent 12 h of SD. Each measurement period included resting supine, seated, and seated performing computerized tasks and measured vigilance and executive function. Subjects were not supine in the periods between measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
270
3
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(320 citation statements)
references
References 53 publications
33
270
3
9
Order By: Relevance
“…The significantly higher SDNN observed following a night of sleep deprivation is in agreement with a study from Viola et al (58). A few studies have reported significantly higher LF/HF and/or normalized LF power (24)(25)(26), a longer NN interval (60), and a lower NN50 (46) during and after total and partial sleep deprivation. Other studies, however, have found no difference in HRV parameters in these conditions (61,62).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The significantly higher SDNN observed following a night of sleep deprivation is in agreement with a study from Viola et al (58). A few studies have reported significantly higher LF/HF and/or normalized LF power (24)(25)(26), a longer NN interval (60), and a lower NN50 (46) during and after total and partial sleep deprivation. Other studies, however, have found no difference in HRV parameters in these conditions (61,62).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, it is thought that the risk for CVD among shift workers may depend on the extent of circadian misalignment and sleep deprivation (21). Although it is thought that sleep deprivation and the risk for CVD are linked (22,23), only a few studies have reported higher sympathetic activity and decreased vasodilatation during and after (partial) sleep deprivation (24)(25)(26).…”
mentioning
confidence: 99%
“…HRV is often combined with other measurement methods like blood pressure, skin temperature etc. to testify certain interpretations in the context of stress measurement (Zhong et al, 2005;Lupien et al, 2006) and emotions (Lupien and Brière, 2000). The consolidation of HRV and EEG data showed that high beta EEG power correlates with increased HRV significantly (Seo and Lee, 2010).…”
Section: Selection Of Methodologies and Instrumentsmentioning
confidence: 99%
“…Mechanismus, jakým nedostatečný spánek přispívá k vysokému tlaku není dosud zcela objasněn. V experimentálních studiích je u spánkově deprimovaných jedinců zřetelné zvýšení sympatické nervové aktivity, zvýšení srdeční frekvence a zvýšení sodíkové retence (Gangwisch et al, 2006, s. 833;Zhong et al, 2005Zhong et al, , s. 2024. Nedostatečná délka spánku je také prokazatelně spojena s poklesem leptinu, se zvýšením ghrelinu a se zvýšením kortizolu, dále se zvýšenou chutí k jídlu a s insulinovou resistencí, které mohou také nepřímo přispívat k hypertenzi (Adámková, 2009, s. 27).…”
Section: Diskuzeunclassified